Comparison of surgical results in patients with hypertrophic obstructive cardiomyopathy after classic or modified morrow septal myectomy. Issue 51 (December 2017) - Lai, Yongqiang; Guo, Hongchang; Li, Jinhua; Dai, Jiang; Ren, Changwei; Wang, Yang
Abstract : Abstract: The study was conducted to evaluate the surgical results in patients with hypertrophic obstructive cardiomyopathy (HOCM) who underwent either classic Morrow septal myectomy or modified procedure. The modified Morrow septal myectomy has gained interest as a new treatment for patients with drug-refractory symptoms of HOCM; however, its benefits in comparison to the classic procedure are unknown. In all, 236 symptomatic HOCM patients underwent surgical treatment from January 2006 to January 2015. Among them, 86 patients were treated by the classic Morrow myectomy and 150 patients via the modified procedure. Septal thickness, maximal left ventricular outflow tract (LVOT) pressure gradient (PG), and the presence of a permanent pacemaker were recorded after operation and follow-up The left ventricular septal thickness (22.1 ± 11.9 vs 17.1 ± 4.0 mm for classic procedure, and 22.3 ± 4.4 vs 16.1 ± 3.5 mm for modified procedure; P  < .001), LVOT velocity (410.6 ± 134.0 vs 210.5 ± 81.4 mm/s for classic procedure, and 432.7 ± 119.3 vs 167.7 ± 50.1 mm/s for modified procedure; P  < .001), LVOT PG (76.0 ± 43.5 vs 19.8 ± 16.7 mm Hg for classic procedure, and 80.8 ± 40.7 vs 12.3 ± 8.5 mm Hg for modified procedure; P  < .001) were significantly decreased after the operation in both groups. The modified group, however, showed significantly greater reduction in these echocardiographic parameters than the classic group. PG was completely eliminated in 142 (94.7%) patients receiving the modified myectomy, and a resting PG over 30 mm Hg was demonstrated in 16 (18.6%) patients in the classic group at follow-up ( P  = .001). Thirty-two (37.2%) patients in the classic groups had a mitral valve replacement, which is significant more than 14 (9.3%) in the modified group ( P  < .001). Both the classic procedure and the modified procedure can reduce LVOT obstruction and alleviate symptoms in patients with HOCM. The modified Morrow septal myectomy is superior to the classic procedure in reducing the LVOT gradient with a lower incidence of mitral valve replacement.